Widespread functional androdioecy in Mercurialis annua L (Euphorbiaceae) - Pannell, J (1997)
The widespread coexistence of male and monoecious (cosexual) plants in Spanish, Portuguese and Moroccan populations of Mercurialis annua, an annual wind-pollinated ruderal, represents an important case of functional androdioccy, a rare breeding system in plants and animals. In M. annua, both mades and cosexes disperse fully competent pollen. Quantitative gender varies discontinuously between males and cosexes, with males producing a mean of 6.09 times as much pollen as cosexes. It appears that gender is determined by a simple developmental switch, with male and cosexual inflorescences differing markedly in morphology: staminate flowers are borne on erect peduncles in males and in tight spiral clusters around a subsessile pistillate flower in cosexes. Males do not differ from cosexes in their biomass, but they are significantly taller, principally as a result of their greater internode lengths. The cosexual inflorescence is strongly protogynous so that outcrossing is favored in dense stands, but seed-set is assured in cosexes isolated from prospective mates because of their ability to self-fertilize. Males typically occur at frequencies o less than about 30% in androdioecious populations, in accordance with theoretical predictions for functional androdioecy. In the guenus Mercurialis, dioecy is the ancestral condition and monoecy and androdioecy, which occur in polyploid populations of M. annua, are derived. I argue here that androdioecy is most likely to evolve in plants (1) from dioecy, (2) in wind-pollinated species, and (3) in species with a colonizing habit. These predictions are also consistent with the limited published data available for other species.